Genome structure and expression - Reymond, Alexandre (Henry Stewart Talks, 2009)
Genome Structure and Expression, Human genetic variation, Variations can be of any scale, Landmarks in the study of human genetic variation, Array CGH, Copy number variations (CNV), CNVs, open questions, Mouse CNV catalog, Validation of HMM, NimbleGen CGH array, CNVs and expression, Variance of expression levels, Correlation between CNV and expression, Hypothesis for CNV and expression correlation, CNV genes are less expressed than non CNV, CNV genes are more specific than non CNV, Brain genes are less likely to be CNV, Proportion of expression variance and CNVs, WBS syndrome, CNV and expression, Variance of flanking genes, mechanisms, The generation and use of recombinant inbreds
Archived at 2021/02/25